Mobilität von Senioren. Ein Segmentierungsansatz als Grundlage zielgruppenspezifischer Angebote. - Haustein, Sonja; Hunecke, Marcel; Kemming, Herbert (Deutscher Verkehrs-Verl., 2008)
Häufig wird im Kontext der Verkehrsforschung festgestellt, dass es sich bei der wachsenden Gruppe der älteren Menschen um eine heterogene Gruppe handelt, was eine differenzierte Betrachtung ihrer mobilitätsbezogenen Voraussetzungen und Einstellungen erfordert. Vor dem Hintergrund der zunehmenden Pkw-Verfügbarkeit von Senioren wird in dem Beitrag ein Ansatz zur Segmentierung älterer Menschen vorgestellt, der die Ableitung von zielgruppenspezifischen Maßnahmen zur Erhöhung der Nutzung öffentlicher Verkehrsmittel ermöglicht. difu

Our ageing society witnesses the senior citizens' group moving ever more foreground. It has often been mentioned that this constantly expanding group is essentially heterogeneous, thus necessitating a subtly differentiated approach during our investigations. The report presents an attempt that is aimed at splitting up the group of elderly people into segments by taking into account such important determinants as their mobility behaviour and related attitudes, the availability of private cars and the age factor. Based on this, a cluster analysis has identified six segments of the senior citizens' group and noted clear differences with regard to the means of transport of their choice, their spare time activities and the level of traffic generated. Against the background of senior citizens' increasing access to private cars, a discussion follows of specific measures aimed at selected groups in order to promote the use of public transport and the resultant impact on future traffic planning and procedures. difu
Keywords: Verkehr; Alter Mensch; Alterung; Mobilität; Verkehrsmittel; Attraktivität; Öffentlicher Verkehr; Verkehrsforschung; Mobilitätsforschung; Mobilitätsverhalten; Älterer Mensch